2012
DOI: 10.1128/jvi.06594-11
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Antiviral Protein APOBEC3G Interacts with HIV-1 Reverse Transcriptase and Inhibits Its Function during Viral Replication

Abstract: cThe cytidine deaminase APOBEC3G (A3G) exerts a multifaceted antiviral effect against HIV-1 infection. First, A3G was shown to be able to terminate HIV infection by deaminating the cytosine residues to uracil in the minus strand of the viral DNA during reverse transcription. Also, a number of studies have indicated that A3G inhibits HIV-1 reverse transcription by a non-editingmediated mechanism. However, the mechanism by which A3G directly disrupts HIV-1 reverse transcription is not fully understood. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 66 publications
(102 reference statements)
2
94
1
Order By: Relevance
“…(ii) APOBEC3 proteins could interact with reverse transcriptase itself (directly or indirectly) and perturb enzymatic function. This model is appealing, since relatively few p66-51 reverse transcriptase dimers would have to be bound and inhibited, and is further supported by recent coimmunoprecipitation studies indicating that A3G can bind to reverse transcriptase in an RNA-independent manner (74). Future efforts will focus on defining this interaction in greater detail and addressing possible mechanisms for enzymatic inhibition.…”
Section: Discussionmentioning
confidence: 91%
“…(ii) APOBEC3 proteins could interact with reverse transcriptase itself (directly or indirectly) and perturb enzymatic function. This model is appealing, since relatively few p66-51 reverse transcriptase dimers would have to be bound and inhibited, and is further supported by recent coimmunoprecipitation studies indicating that A3G can bind to reverse transcriptase in an RNA-independent manner (74). Future efforts will focus on defining this interaction in greater detail and addressing possible mechanisms for enzymatic inhibition.…”
Section: Discussionmentioning
confidence: 91%
“…We observed that reverse transcription was more inhibited by packaged APOBEC3 in mutant than WT virions in EnRT assays. A recent study suggests that APOBEC3G interacts with the reverse transcriptase of HIV-1 (51). Whether this is also the case for MLV's reverse transcriptase and APOBEC3 and whether there is differential accessibility of reverse transcriptase to the viral RNA in mutant viruses remain to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…The coding region for the RT gene was obtained by digesting a CMV-T7-RT expression vector with BamHI and BglII restriction enzymes. The CMV-T7-RT expression vector has been described earlier (35). A ProLabel (PL)-DYNLL1 expression vector was constructed by subcloning the DYNLL1 gene into a CMV-PL-Ku70 expression vector at BamHI and NotI restriction enzyme sites, by replacing the Ku70 gene.…”
Section: Methodsmentioning
confidence: 99%